The Application of Potato Starch-Based (Amylum solani) Edible Coating on Tomatoes (Solanum lycopersicum L.) - Bimantio, Mohammad Prasanto; Wulandari, Astri; Partha, Ida Bagus Banyuro (Universitas Ahmad Dahlan, 2025)
This study investigates the potential of potato starch-based edible coatings (Amylum solani) to extend the shelf life and preserve the quality of tomatoes (Solanum lycopersicum L.) during storage. The experiment contributed to evaluating the effect of the coating on critical quality parameters, including weight loss, firmness, color stability, moisture content, vitamin C retention, and sensory characteristics. Tomatoes with edible coatings exhibited a slower rate of weight loss compared to uncoated samples, which is attributed to the coating's ability to form a protective barrier that minimizes water evaporation and respiration rates. Coated tomatoes also retained firmness more effectively, delaying the softening process caused by metabolic and enzymatic activity. The study revealed that the edible coating reduced the rate of color degradation by slowing the loss of chlorophyll and the formation of lycopene, preserving the tomatoes' visual appeal. Moreover, the coating significantly delayed the decline in vitamin C content by inhibiting oxidation and maintaining structural integrity, which was further reflected in the higher sensory scores for coated tomatoes. Organoleptic tests indicated that panelists preferred coated tomatoes due to their glossy appearance, firmer texture, and sweeter taste, although these preferences gradually decreased over time. Analysis showed that the coating extended the shelf life of tomatoes to 13.64 days, compared to 9.76 days for uncoated samples. These results highlight the efficacy of potato starch-based edible coatings as an environmentally friendly and cost-effective solution for reducing postharvest losses, meeting consumer demand for fresh produce, and improving food security. This study provides valuable insights into the practical application of edible coatings for preserving climacteric fruits such as tomatoes, with implications for sustainable agricultural practices.